Nurture-U student mental health longitudinal survey: a study protocol - Kate E Saunders; Samuel R Chamberlain; Jemima Dooley; Edward R Watkins; Liz Forty; Sarah Rees; Anne C Duffy; Anthony Quinn; Ellen Marshall; Lucy Dorey; Kevin A Matlock; Alexandra Newbold; et al. (BMJ Open)
Introduction University life represents a critical period for young adults, providing opportunities for personal growth and development of coping skills but also posing significant mental health challenges. Recent trends indicate rising mental health concerns among university students, exacerbated by the COVID-19 pandemic and its aftermath. This study aims to address gaps in longitudinal data on student mental health in the UK and to identify risk and protective factors across diverse student populations.Methods and analysis The current Nurture-U survey is developed from the U-Flourish biannual survey study piloted at Queen’s and Oxford universities in Canada and the UK, respectively. Nurture-U is a longitudinal survey study conducted at five UK universities, aiming to create a comprehensive data set from over 5000 students. The study will collect data at the start and completion of each academic year, using validated measures to assess well-being, mental health symptoms, lifestyle factors and access to support. Recruitment will target all students, with an emphasis on first-year students, to track their mental health trajectory from university entry through subsequent years.Ethics and dissemination Ethical approval has been obtained from relevant committees at each participating university. Students will provide informed consent prior to participation, with risk messages and support information provided for those indicating self-harm or suicidal thoughts. Data will be de-identified and securely stored, with results disseminated through academic publications, social media and student engagement activities.